EnvZ functions through OmpR to control porin gene expression in Escherichia coli K-12. - Slauch, J M (1988)
The regulatory proteins OmpR and EnvZ are both required to activate expression of the genes for the major outer membrane porin proteins, OmpF and OmpC, of Escherichia coli K-12. Here we show that OmpR, under certain conditions, could activate porin expression in the complete absence of EnvZ. In addition, the pleiotropic phenotypes conferred by a particular envZ mutation (envZ473) required the presence of functional OmpR protein. These results lead us to conclude that EnvZ and OmpR act in sequential fashion to activate porin gene expression; i.e., EnvZ modifies or in some way directs OmpR, which in turn acts at the appropriate porin gene promoter.